Morphological and Histological Study of Thyroid Gland in Felis Catus (Linnaeus,1758) - Jaafer Hammodi, Noor Mohammed; Al Aamery , Rana Alaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The results of the current study showed that the thyroid gland in an adult domestic cat (Felis catus) is located in the neck area on both sides of the trachea at rings 1–5. The gland consists of two lobes (right and left), and it is surrounded by a capsule of connective tissue consisting of two outer and inner layers, and a layer of fatty tissue overlaps with the outer layer of the capsule. In addition, the results of this study found that the histological structure of the thyroid gland is composed of several follicles that appear in different sizes and shapes. The follicles are lined with simple cuboidal epithelial tissue and sometimes appear lined with high and low simple cuboidal epithelial tissue. The gland is histologically composed of two types of cells: epithelial cells and parafollicular cells, or calcitonin cells (C-cells), the latter being few in number compared to the epithelial cells and appearing as single cells or forming clusters in two locations: the first is between the follicular and the second is intrafollicular.